2010
DOI: 10.1002/ejoc.200901404
|View full text |Cite
|
Sign up to set email alerts
|

First Asymmetric Synthesis of Boehmeriasin A

Abstract: The first asymmetric synthesis of phenanthroquinolizidinealkaloid (R)‐boehmeriasin A is described. Two alternative synthetic pathways to the key intermediate (RS,R)‐4 were achieved through a combination of highly diastereoselective 1,2‐nucleophilic addition on (–)‐(S)‐1‐amino‐2‐(methoxymethyl)pyrrolidine hydrazones with a ring‐closing metathesis to ensure the construction of the piperidine template. A subsequent acylation/oxidation/aldol condensation/radical cyclization sequence completed the assembly of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The (R)-and (S)-enantiomers were obtained in enantiomeric ratios of 97.5:2.5 and 98:2, respectively. By comparison with the literature, 48,50 we confirmed that the (R)-product is the natural product. Finally, we tested our synthetic compounds in three cancer cell lines, with paclitaxel as a control (Table 6).…”
Section: Total Synthesis Of (R)-and (S)-boehmeriasin Asupporting
confidence: 77%
See 1 more Smart Citation
“…The (R)-and (S)-enantiomers were obtained in enantiomeric ratios of 97.5:2.5 and 98:2, respectively. By comparison with the literature, 48,50 we confirmed that the (R)-product is the natural product. Finally, we tested our synthetic compounds in three cancer cell lines, with paclitaxel as a control (Table 6).…”
Section: Total Synthesis Of (R)-and (S)-boehmeriasin Asupporting
confidence: 77%
“…48 This compound was found to be more potent than paclitaxel in most cancer cell lines, with GI 50 values ranging from 0.8 to 265 nM. 49 Because the configuration of the stereocenter of boehmeriasin A was unknown at the time when we began our study, 50 we synthesized both enantiomers of the compound. We adopted a similar strategy to that which we used in our synthesis of ipalbidine, and we obtained triflate 5.12 in two steps from enaminone 5.9 (Scheme 47).…”
Section: Total Synthesis Of (R)-and (S)-boehmeriasin Amentioning
confidence: 99%
“…5 While these studies were based essentially on Cryptopleurine (1) as the alkaloid model, the more recent Boehmeriasin-A (4) based compounds have shown in in vitro study anti-proliferative activity in three cancer cell lines (CEM, HeLa, and L1210) and in two endothelial cell lines (HMEC-1, BAEC) at concentration near the nanomolar range. 6,9 Beyond other racemic experimental protocols 10 an alternative and interesting approach based on the construction first of chiral polycyclic systems containing piperidine-2-methanol (AeD) was also developed. 6 Out of such considerations, the synthesis of these natural products and derivatives has been an appealing area of research.…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic methodologies have been developed for the elaboration of some boehmeriasin A congeners (e.g. cryptopleurine and its hydroxy derivatives) in both racemic and optically active forms [4][5][6][7][8][9][10][11][12][13][14][15] Herein, we report two synthetic approaches to obtain the racemic mixture and the pure enantiomers of boehmeriasin A. Biological evaluation showed high anti-proliferative activity on cancer and endothelial cells with topoisomerases and SIRT2 as involved targets.…”
Section: Introductionmentioning
confidence: 99%